MENINGKATKAN KREATIVITAS SENI MELALUI PERMAINAN KOLASE AMPAS KELAPA ANAK USIA DINI DI PAUD AL-FAIZ KOTA LANGSA - Nina Rahayu, Nina Rahayu (At- Tarbawi, 2020)
The problem on this study is that it is still lack of child creativity particularly in the arts. This can be seen from children who are not yet able to discriminate color and name color precisely as well as the use of less supportive game media in the development of child creativity. The purpose of the study was To figure out how to increase child art creativity through coconut amply collage games. The type of research used is qualitatively descriptive. Paud Al-Faiz's child research subject Paya Bujok Tunong Langsa numbered 10 group B children and research objects increased creativity through coconut dregs games. The instruments used on research through observation, interviews and documentation. As for the research results in this study that is, there is an increase in child art creativity while playing collage game. 90% of children who have started to be able to work on activities according to teacher intruction and are able to work according to indicators.